Global flood hazard : applications in modeling, mapping and forecasting - Schumann, Guy J-P. (Hoboken, NJ : John Wiley & Sons, 2018)
'Global flood hazard modeling and forecasting has many challenges but at the same time there is a lot of room for development and opportunities along the way for addressing these challenges, which recent advances in global flood hazard mapping, modeling, and forecasting evidently demonstrate. Efforts to advance the fields should focus on achieving better accuracy of global model boundary data sets such as precipitation estimates, streamflow simulation, digital elevation models, and also correct implementation of local scale features highly important for flood propagation. This would increase our current ability to simulate floodplain inundation at the global scale more accurately. Output usability of models can be improved by integrating global models efficiently with remotely sensed observations of floods. Thus, there is a need not only to understand the limitations and errors of data and methods but also to develop more sophisticated data processing algorithms, as well as robust frameworks for handling the many heterogeneous geospatial data sets and for effective information management. Despite the many challenges that exist at present and need to be overcome, the science and applications of global flood hazard estimation is currently a fast-moving field with much more significant progress to be expected in upcoming years' -- Provided by publisher's website
Includes bibliographical references.
Keywords: Flood forecasting; Flood damage prevention; Floodplains -- Monitoring